Influence of Quartet Card Media on Students' Learning Interest in Social Sciences Subjects of Grade VII at SMP Negeri 21 Samarinda - Pitriyani Ramli; Rizal Izmi Kusumawijaya (JESS (Journal of Educational Social Studies), 2026)
This research was motivated by the low learning interest of students in Social Studies subjects at SMP Negeri 21 Samarinda, caused by the dominance of lecture methods and the use of textbooks. This study aims to determine the effect of using quartet card media on the learning interest in Social Studies of Grade VII students at SMP Negeri 21 Samarinda. This research uses a quantitative method with a quasi-experimental design (Nonequivalent Control Group Design). Data analysis techniques used the Independent Sample T-Test and Effect Size test with the help of SPSS version 29. The results showed a significance value of 0.001 < 0.05, so H₀ was rejected and Hₐ was accepted, and the Effect Size test produced a value of 0.835, which falls into the high effect category. The novelty of this research lies in three aspects: (1) the application of quartet card media in Social Studies learning at the junior high school level, a context that is still limited. (2) This research contributes theoretically by operationalizing learning interest indicators—interest, attention, engagement, and enjoyment—within the framework of game-based learning to enrich the understanding of how interactive media fosters students' learning interest. (3) methodological contribution through the use of the Effect Size test to measure the magnitude of the effect, which is still rarely applied in similar studies. The contribution of this research is to provide an alternative learning media for teachers to foster students' interest in learning Social Studies.